Problems of excellence in philosophy of al-Farabi and al-Gazali - Бухаев, Амиржан (Eurasian Journal of Religious Studies, 2017)
In this article authors try to consider as understand perfection and ways of his achievement of al – Farabi and al – Gazali. Thinkers of the East noted in the treatises natural aspiration of the person fortunately, and happiness is understood al-Farabi as a certain degree of perfection, as a certain perfect purpose.The problem of achieving a certain perfection in the east of the medieval Arab-language philosophy and theology is one of the central places. Philosophers have come from the fact that to achieve a certain degree is possible only through an internal struggle. Search of an adequate solution of the problem of spiritual moral improvement in philosophy al-Farabi and al-Gazali is connected with search of ways of a certain perfection. Thinker unanimous in the view that to achieve perfection you must first of all examine the essence of man, his qualities. Perfection eastern thinkers presented as a goal. But in the understanding of how to achieve this goal philosophers disagree.